Smart Home Design Using IoT - Kashypa, Raushan (International Journal of Computer Sciences and Engineering, 2020)
Energy saving has become prime concern everywhere. When we talk about it, the first thing that comes in mind is Smart Grid. Smart Grids the perfect solution for saving and optimizing the energy usage. IoT do not need any introduction in the current scenario. IoT technology helps in checking the proper usage of energy. In this paper, the focus is given on the design of smart home that will use smart grid coupled with IoT technology. The working of this system, protocols used by this system and challenges of the same is discussed in this paper.